Analyzing junior high school students’ mathematical creative thinking skill in mathematical modelling - Ramadani, Iqbal; Wulandari, Nidya Ferry; Triliana (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2021)
Creative thinking skills are one of the skills that must be developed in order to pursue developments in the 21st century. The development of creative thinking skills must be applied within a formal education level. One of the areas of study taught in formal education is mathematics. Mathematics can be used to solve problems in everyday life by using mathematical modeling. This study aimed to analyze the students' mathematical creative thinking skills in mathematical modeling with descriptive design. The steps on this research consisted of designing a test of creative thinking skills; Interviewed test results of mathematical creative thinking skills; and analyzed student answers results on mathematical creative thinking skills tests. The subject of the study consisted of 65 of junior high school students of class VIII. Findings demonstrate the skills of creative thinking students in modeling in the category of students with high mathematical abilities is that students can create unique models and seek solutions using different ways with logical and systematic, in medium category, students have a tendency to use trial and error methods as well as procedural ways to test models made, while in low category, students tend to use trial and error Test the model and resolve the problem.